Abnormalities of the Corpus Callosum in autism subtype. (15th May 2008) - He, Qing; Duan, Ye; Miles, Judith; Takahashi, Nicole
Brain imaging studies of the Corpus Callosum (CC) in autism have yielded inconsistent results. This paper explores the CC abnormalities in autism. The CC is segmented from 2D MRIs using our newly developed semiautomatic method, and a subsequent contour stitching is performed to create the 3D surface of the CC. After alignment, differences between autistic patients and the control group are computed using Hotelling T2 two-sample metric, which results in a raw significance map. Permutation test is performed to generate a corrected significance map. The statistical results reveal significant difference between patients and controls in the body of the CC.